Artikel Pengaruh Kepemimpinan Kepala Sekolah Dan Profesionalisme Guru PAI Terhadap Motivasi Belajar Siswa - Muhroji Muhroji (MGMP PAI SMP BINTAN, 2022)
This study generally aims to study the factors that influence students' learning motivation. By using the participatory action research method, then specifically we tried to find out the influence of principals' leadership and professional competence of PAI teachers on students' learning motivation in Islamic Religious Education subjects. The data source used is statistical analysis using interval, ordinal and nominal data. The research participants were 45 students of class VIII SMP in Bintan Regency, Riau Islands. The results obtained by the researcher that there is a correlation between the principal's leadership and the professional competence of PAI teachers on students' learning motivation for Islamic Religious Education subjects. And it is hoped that the results of this study can be a positive contribution to improving the quality of Islamic Religious Education learning.